Review of the high bed–low ditch system as an alternative to lowland paddy in tropical and subtropical Asia - Zhao, Fei; Luo, Shiming; Zhang, Jiaen (Frontiers in Sustainable Food Systems, 2024)
Many forms of traditional raised bed systems could be found around the world. Several of them have been identified as Globally Important Agricultural Heritage Systems (GIAHS) sites by Food and Agriculture Organization of the United Nations. Unlike traditional raised bed systems with similar structures in the Americas, the high bed–low ditch (HBLD) system in tropical and subtropical Asia, which is originated and developed from rice production, has been playing an important role in enhancing food security and maintaining farmer livelihood for centuries. Moreover, products provided by HBLD system are not only important for the livelihood of the local farmers, but also important for people living in the nearby towns and cities especially for vegetable and fruit supply. In this system, the ditches or sunken beds can be used to lower the groundwater table, retain nutrients and soil particles washed from the bed, grow rice or aquatic vegetables, and raise fish or shrimp. The HBLD system can also help to reduce salinity in coastal lowlands due to the presence of ditches. The raised beds can be used to grow various upland crops. Compared with rice monocropping, the adoption of HBLD system significantly improves the cropping intensity, productivity, employment, and income of farmers. Famers’ long-term practices fully demonstrate that this system is a type of sustainable agriculture with strong adaptability to the changes of natural environment. However, it should also be noted that the large-scale development of HBLD systems is not simply dependent on natural conditions, but is also determined by specific socioeconomic factors, such as good transportation facilities, a well market system, and a sufficient supply of labor. As a model of equilibrium between food production and high levels of biodiversity maintenance, the HBLD system is an important agricultural heritage system with global significance, and it should be well preserved and utilized in new ways to realize its important multiple functions under conditions of rapid urbanization in lowland and coastal regions.